Registration of three soft red winter wheat germplasm lines with exceptional milling and cookie baking performance. Issue 3 (21st August 2020) - Meier, Nicholas A.; Malla, Subas; Oakes, Joseph C.; Murphy, J. Paul; Baik, Byung‐Kee; Chao, Shiaoman; Griffey, Carl A.
Abstract: The release of soft red winter wheat ( Triticum aestivum, L.) germplasm lines VA11DH‐P46xTrib‐28 (Reg. no. GP‐1048, PI 691656), VA11DH‐P46xTrib‐99 (Reg. no. GP‐1049, PI 691657), and VA11DH‐P46xTrib‐103 (Reg. no. GP‐1050, PI 691658) is intended to provide breeders with genetic material having exceptional milling and baking quality performance. The quantitative nature of milling and baking performance makes improvement and early generation selection difficult. Marker assisted and genomic selection breeding schemes can be improved by introducing breeding material with superior end‐use quality and use of known predictive DNA markers. These three lines have acceptable agronomic performance with grain yields (4605–5733 kg ha −1 ) similar to or higher than those of Pioneer '26R46' (4568 kg ha −1 ). The lines have exceptional milling and baking performance with mean flour yields (733–736 g kg −1 ), softness equivalence (550–573 g kg −1 ), flour protein (89–94 g kg −1 ), solvent retention capacity for lactic acid (1162–1189 g kg −1 ) and sodium carbonate (672–697 g kg −1 ), and cookie diameters (19.1–19.5 cm) that are better than or similar to ( p  < .05) those of Pioneer 26R46 (721 g kg −1, 531 g kg −1, 93 g kg −1, 1221 g kg −1, 703 g kg −1, and 18.9 cm).